Effects of Par on Plant Spacing in Relation to Yield Efficiency in Peach (Bangladesh Journal of Botany, 2021)
Effects of PAR in relation with plant spacing in peach cultivar ‘Shan-i-Punjab’ during the year 2013-14 and 2014-15 were evaluated. The trees were trained to 4 different training systems and each system consisted of 2 spacings viz., 5 × 3 m and 5 × 2 m. Daily PAR was recorded at morning, midday and evening and it was found that irrespective of planting distance maximum light interception was recorded at midday hours. Plants spaced at 5 × 3m received more light inside the canopy during full day which directly influenced number of fruits per tree, number of picking, fruiting density, yield efficiency, relative pattern of fruit maturity whereas, fruit yield per hectare was maximum in 5 × 2 m.Bangladesh J. Bot. 50(3): 701-707, 2021 (September)